Proteomic analysis reveals how pairing of a Mycorrhizal fungus with plant growth‐promoting bacteria modulates growth and defense in wheat. (25th March 2021) - Vannini, Candida; Domingo, Guido; Fiorilli, Valentina; Seco, Daniel Garçia; Novero, Mara; Marsoni, Milena; Wisniewski‐Dye, Florence; Bracale, Marcella; Moulin, Lionel; Bonfante, Paola
Abstract: Plants rely on their microbiota for improving the nutritional status and environmental stress tolerance. Previous studies mainly focused on bipartite interactions (a plant challenged by a single microbe), while plant responses to multiple microbes have received limited attention. Here, we investigated local and systemic changes induced in wheat by two plant growth‐promoting bacteria (PGPB), Azospirillum brasilense and Paraburkholderia graminis, either alone or together with an arbuscular mycorrhizal fungus (AMF). We conducted phenotypic, proteomic, and biochemical analyses to investigate bipartite (wheat–PGPB) and tripartite (wheat–PGPB–AMF) interactions, also upon a leaf pathogen infection. Results revealed that only AMF and A. brasilense promoted plant growth by activating photosynthesis and N assimilation which led to increased glucose and amino acid content. The bioprotective effect of the PGPB–AMF interactions on infected wheat plants depended on the PGPB‐AMF combinations, which caused specific phenotypic and proteomic responses (elicitation of defense related proteins, immune response and jasmonic acid biosynthesis). In the whole, wheat responses strongly depended on the inoculum composition (single vs. multiple microbes) and the investigated organs (roots vs. leaf). Our findings showed that AMF is the best‐performing microbe, suggesting its presence as the crucial one for synthetic microbial community development. Abstract : We investigate local and systemic effects on wheat caused by two plant growth promoting bacteria alone and upon co‐inoculation with an arbuscular mycorrhizal fungus. Overall, our results indicate that while AMF promotes both plant growth and immunity, the PGPB differentially modulates the effect of AMF on these plant processes.